Validating the Measures of Emotional Intelligence-Based Performance Theory in the Context of Academic Staff at Kyambogo University, Uganda - Kato, Joshua Kimata; Mugizi, Wilson; Kyozira, Peter; Ariyo, Gracious Kaazara (Uganda East African Journal of Interdisciplinary Studies, 2024)
The study validated the measures of Emotional Intelligence Based Performance Theory in the context of full-time academic staff at Kyambogo University. Basing on the conceptualization by Goleman (1998), Emotional Intelligence Based Performance Theory was studied in terms of self-awareness, self-management, social awareness, and relationship management. This cross-sectional study involved a sample of 201 from full-time academic staff at Kyambogo University, data were collected using a self-administered questionnaire. Descriptive statistics and structural equation modelling (SEM) using Smart PLS for partial least square structural equation modelling (PLS-SEM) were used to determine the measures of Emotional Intelligence Based Performance Theory. Descriptive results indicated that four constructs of Emotional Intelligence Based Performance Theory of self-awareness, self-management, social awareness and relationship management were high. PLS-SEM indicated that the four constructs of self-awareness, self-management, social awareness and relationship management were appropriate measures of the Emotional Intelligence Based Performance Theory. It was concluded that Kyambogo University managers need to promote a high level of self-awareness, self-management, social awareness and relationship management among academic staff. Therefore, the study recommended that Kyambogo University managers need to emphasise self-awareness, self-management, social awareness and relationship management among full-time academic staff.